2022
DOI: 10.11648/j.sjc.20221002.11
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antimicrobial Activities of Limonene with Mineral Carriers in LDPE Films for Active Packaging Application

Abstract: The integration of essential oils (EOs) into polymers to endow antimicrobial properties has received a lot of attention. EOs are remarkable in that they have broad antimicrobial activity from a natural source while also being volatile. Their volatility, on the other hand, makes high-temperature processing techniques difficult to incorporate into polymers. In this study, active films based on low-density polyethylene (LDPE) and limonene essential oil (LEO) were prepared and characterized. Before incorporation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
4
1
Order By: Relevance
“…The obtained TO@HNT nanohybrids were loaded in LDPE via a melt-extrusion preparation process at 5, 10, and 15 %wt. nominal contents, which were higher compared to those reported in the literature [ 15 , 16 , 17 , 18 , 19 ]. Such high contents of HNT and/or TO@HNT nanofillers, to the best of our knowledge, are reported for the first time.…”
Section: Introductioncontrasting
confidence: 68%
See 2 more Smart Citations
“…The obtained TO@HNT nanohybrids were loaded in LDPE via a melt-extrusion preparation process at 5, 10, and 15 %wt. nominal contents, which were higher compared to those reported in the literature [ 15 , 16 , 17 , 18 , 19 ]. Such high contents of HNT and/or TO@HNT nanofillers, to the best of our knowledge, are reported for the first time.…”
Section: Introductioncontrasting
confidence: 68%
“…essential oils concentration that exhibited a higher inhibitory effect than the films obtained using the ionizing treatment. Recently, researchers proposed adsorption of EOs in nanoclays, such as montmorillonite (Mt) and Halloysite nanotubes (HNT), to develop a hybrid EO/nanoclay nanostructure and incorporation of such hybrids into the LDPE matrix [ 15 , 16 , 17 , 18 , 19 ]. Nanoclays such as HNT act as nanoreinforcements, barrier agents, and EOs nanocarriers according to this method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothesis tests were carried out via the ANOVA method, using the Tukey criteria for equal-variance assumptions, setting confidence intervals at 95% and significance levels at p < 0.05. In addition, the assurance of mean equality (EA%) or inequality (IA%) was examined based on empirical equations previously reported in the literature [ 55 ]. Across all tests, it was observed that the mean values of the various sample properties that were statistically different exhibited an inequality assurance factor (IA%) of over 56%, while the mean values that were statistically equal exhibited an equality assurance factor (EA%) of over 61%.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature there is a plethora of studies with EOs addition on polymers such as polyethylene (PE), low density polyethylene [7][8][9], polyethylene tetraphthalate (PET) [10], polystyrene (PS) [11] and biopolymers such as starch, chitosan, gelatin, alginates, poly-lactide acid (PLA) active packaging films [12][13][14][15][16][17][18][19][20]. In addition, there are many studies with use of EOs active components in active packaging systems such as limonene, eugenol, thymol, cinnamaldehyde and carvacrol [21][22][23][24][25][26][27][28]. Carvacrol (CV) is a phenolic monoterpenoid found in EOs of oregano (Origanum vulgare), thyme (Thymus vulgaris), pepperwort (Lepidium flavum), wild bergamot (Citrus aurantium bergamia), and other plants and is useful for its significant antibacterial, antifungal, antimicrobial, and antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%